Architecture and the climate: An analysis from a bioclimatic point of view of the Solaris Building project by architect Ken Yeang - Domingues , Quétilan Rodrigues; Souto , Ana Elisa Moraes; Sherer, Minéia Johann (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The works of Ken Yeang, an architect widely recognized for his work in what is known as “green architecture”, stand out for the fact that they are designed taking into account the climatic conditions of the places where his projects are implemented. In this sense, his works are aligned with the concept of bioclimatic architecture, which aims to design buildings adapted to the climate of each region. This article aims to characterize the climate of the city of Singapore and analyze the bioclimatic strategies applied to the Solaris building, evaluating whether these strategies meet local climate needs. The analysis methodology consisted of reviewing project documents, descriptive documents and images available on the website of the architects responsible for the work. The research results reveal the conscious use of certain elements in the building, corroborating the principles of bioclimatic architecture.